Sonatines Choisies : Selected Sonatines-Ausgewahlte Sonatinen 3 - FERTE, Armand (Schott Freres, 1948)
Di dalam buku ini terdapat 8 lagu: Handrock J. Op. 66 no 1; Gurlitt C , Op.54 No.2; Handrock J.Op. 66 No 2; Mozart, W.A do maj.; Gurlitt C, Op. 54 No 6; Berens H. op. 81 no. 5; Mozart W.A.la maj; Kircher T. op.70 No. 2